Dialog Nabi Musa dengan Allah pada Surah Asy-Syu’ara’ (Kajian Stilistika) - Muhamad Bustanul Arifin; Nur Fauziah Fatawi (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2021)
Prophet Musa is one of the prophets who are said by the masterof Al-Qur’an translation having a direct dialogue with Allah SWT. On the other side prophet Musa is an ordinary human who socializes with other. The case in this study is how is the language style of Musa when having a dialogue with Allah. Reading dialogue of prophet Musa with Allah SWT in the Qur’an especially in surah asy-Syu’ara’ uses helping science they are stylistic and intertextual. The limited of this study are the phonology analysis, lexical, figure of speech, context and cohesion and how these five things are used as tools of communication.The analysis of verses about the dialogue Musa with Allah SWT uses a direct sentence including the structure of informative text. The language style when Musa had a dialogue with Allah SWT is very hyperbolic because Musa had gotten psychological pressure and was strengthened used the rhyme pattern "un." The results using intertextuality is found a similarity of verses are uncommon in Arabic in surah asy-Syu'ara’ with the common Arabic composition in the Surah Taha.